Şırnak İli Kömür Üretimi İş Kolunda Faaliyet Gösteren Firma Sahiplerinin SosyoEkonomik Durumlarına Genel Bakış– 2010 - Darıcı, Bülent; Öcal, Fatih Mehmet; Okyar, Mete Cüneyt (Selcuk University, 2011)
Ülkemiz, yeraltıkaynaklarıaçısından oldukça zengin bir ülkedir. Diğer ülkelerde olduğu gibi ülkemiz de zengin maden yataklarından çıkardığımadenleri, sanayi sektörü için hammadde olarak kullanmaktadır. Ancak şu an çıkarılan madenler, madencilik sektöründe yaşanan birtakım sorunlar nedeniyle istenilen seviyenin altında seyretmektedir. Madencilik sektörü, bağlantılıolduğu sektörler göz önüne alındığında kalkınmanın en önemli ana unsurlarından bir tanesidir. Madencilik sektörü denilince ilk akla gelen özellikler arasında, risk unsurunu fazlaca içinde barındırması, önemli miktarda sermaye ihtiyacının bulunmasıve yapılan yatırımların geri dönüşsüresinin uzunluğu sayılabilir. Madencilik sektöründe dezavantajlıpek çok durum vardır. Bu durumların önemli bir kısmı, sektörün çevresel etkenlere bağlılığı maden yatağının dağlık bölgelerde ve alt yapıhizmetlerinden yoksun olan bölgeler olması sonucu ortaya çıkmaktadır. Ülkemizde madencilik sektörüne bakıldığında, dünya çapında çıkarılan maden çeşitliliği göz önüne alındığında önemli bir çeşitliliğe sahip olduğu söylenebilir. Ancak, bu çeşitlilik maden çıkarımısöz konusu olduğunda kendisini göstermemektedir. Ülkemizde çıkarılan belli başlımadenler arasında, bakır, demir, bor mineralleri, krom, boksit, kükürt, civa, kömür vb. sayılabilir. Ülkemizde çıkarılan madenler arasında kömür madeni kullanım yerlerinin çeşitliliği de göz önüne alındığında, önemli bir yere sahiptir. Bu çalışmada, Şırnak ilinde madencilik sektörünün bir alt kolu olan kömür üretimi alanında faaliyet gösteren firmaların sahiplerinin 2010 yılıbaşıitibariyle Sosyo-ekonomik durumlarının ortaya konulmasıamacıyla yapılan anket uygulamasıve sonuçları, elde edilen veriler doğrultusunda analiz edilmeye çalışılmıştır. Anket uygulamasında 2010 yılıbaşıitibariyle Şırnak ilinde kömür üretimi alanında faaliyet gösteren toplam 40 firmanın tamamına yakınına ulaşılarak uygulamaya katılmalarısağlanmıştır. Anket çalışmalarında zaman serisi ve yatay kesit veri türlerinden herhangi bir tanesi kullanılabilir. Bu çalışmada 2010 yılıbaşıitibariyle firma sahiplerinin Sosyo-ekonomik durumlarının bilinmesi amaçlandığıiçin yatay kesit veri türü kullanılmıştır.

Our country is rich for it’s natural resources., Our country uses the mines extracted from the rich mineral deposits as raw materials in the industrial sector just like the other countries. Unfortunately, the mines, which have been extracted nowadays, are under the desired level because of some kind of problems in mining industry. When compared to the sectors connected to it, mining industry is one of the key facts of devolopment. When it comes to the the mining industry, such factors as including pretty much risk factor, the need for capital in great amounts, the length of the time for the return of the investments, come to the mind first. There are lots of disadvantageous conditions in extractive industry. The essential parts of these conditions depend on the enviromental factors The location of the mineral deposits in the uplands of mountaneous regions and in the regions which are devoid of suitable infrastructures . It can be said that our country has an important variety of mines for the mining industry especially when it compared with the variety of mines mined worldwide. But this variety reveals itself, only when the topic is extracting mine. Such mines as copper, iron, boron minerals, chromite, bauxite, sulfur, mercury, coal and etc. can be counted a mong the major mines that are extracted in our country. When areas of usage are taken into account, the coal has an important place a mong the metals that extracted in our country. The business, operate in the extracting sector, face with lots of problems during the extracting process. Although, they have differences between open pit reserves and underground mining companies; most of these problems depend on constructional and legistational reasons. The open pit businesses face with ‘’dekapai pickling ’’ problems, while the coal businesses that operates underground deals with the problems depending upon deficiency of technology and managment mentality. The existence of these kind of problems have great effects on the cost of extracted mine through increasing the costs. At the same time, that removes the competition advantage. In this study the data, obtained from the survey, whose aim was to prove the socio-economic statues of the owners of the companies operating in the field of coal production as a sub-branch of the mining sector in Şırnak city at the beginning of the year 2010, is tried to be analyzed. In this survey, nearly all of the 40 companies operating in the field of coal production from the beginning of 2010 in the province of Şırnak have been reached and had them take part.In the survey studies, any of the data types of time series and horizantal sectional can be used. In this study, the horizantal sectional type is used as the intention is to know the socio-economic statues of the owners of the companies operating since the beginning of the year 2010. After the explanation of the purpose, importance, scope of the survey,intended to explain the socio-economic status of the company owners in the field of coal production in Şırnak,it was handed in January of 2010, by specifying that it will be taken in March. This survey, whose aim is to show the socio-economic statues of the owners of the coal companies operating in Şırnak city, was given to the owners of the companies in January after the explainations of its aim, importance, content and how to fill it and would be taken back in March. In March, the survey forms were checked and taken back after filling the missing places. The datas obtained from the survey forms were transferred to the MS Office Excel program and then analyzed with the Statistical Package for Social Sciences 15.0 programme. SPSS-Statistical Package of Social Sciences . Such techniques as the frequency tables, cross tables, charts, ANOVA, independent sample t test, chi-square test, correlation analysis were used as the analysis techniques. In the comparison of the two different groups, TSE certified- non-certified ones, those who give -service training- who do not the independent sample t test is used and determined wheter there is a meaningful difference or not. While comparing more than two groups, such as primary school graduate -elementary school graduate-high school graduate ,the average of the groups for certain topics is compared by using Anova analysis of variance and determined wheter there is a meaningfulful difference or not. To determine the relationship between two variables,the chi-square tests were used. To determine whether there is a significant relationship between two or more numeric variables, the correlation analysis was conducted. After the analysis of the reliability of the survey questions; the value of Cronbach's alpha was calculated as 0.715. The survey questions are reliable when you look at the value, and there is no question that reduces the reliability and necessity to remove any of the questions from the survey. All of the 40 firms that operate in the field of caol production in Sırnak have ben reached. 36 %90 percent of these firms participated in the survey while 4 %10 of them did not. High participation rate, provided benefits to the determination of the problems in a large extent. The density of the labor pover in the branch of the coal business establishments in the province of Şırnak is heaped up the ages between 30 and 49. The reasons such as capital shortage and the rapid rate of return on investment lead young entrepreneurs to shift to other business lines. Beacuse of the difficulties of the work, the fifty year and older entrepreneurs, leave the bussiness branch and join the ones in which they can earn more in less time. 30 of the surveyed firms 83.3% are from Şırnak. The obtained conclusion is that; the people from Şırnak invest in their own land. However, that does not reflect the truth completely or reflect it incomplete. The inability to make the companies, operating in mining coal and energy sector in our country, especially in the provinces close to Şırnak, invest in Şırnak city, proves the failure in the announcement of the advantages of this region in coal mining in the national scale. The expected potential for extracting the coal reserves could not be reached and for this reason it could not make the desirable of effect on the employment level of the city. For the announcement of this city and of the potential of the coal mine on national and regional scales, all nongovermental organizations must act togetler. The characteristics of the firms, 29 of them % 80,5 are functioning as companies limited, incorporated company , 7 of the left % 19,5 are functioning as private companies, can be interpreted as they have covered a distance in the institutionalisation process and besides, it is possible to attribute this fact to such factors as the easy terms of tax payments of the firms, the advantages in participating in the tender bids and the image of being a company. Owners of firms operating in the field of coal production in Sirnak was examined in terms of incorporation firms, the establishment of 17 companies 47.2% in the form of partnership can be associated with the desire of combining their capital to cope with high costs, both general and possible economic crises and being financially stronger. The remaining 19 firms’ 52.8% response has been in the form of "Other" Self-employed . This result explains the short life-span of this firm as the result of constituting coal companies without specialization and a fundamental structure. Constructing The Mining Department in the Vocational High School will help to eliminate this problem. When the owners of firms operating in the field of coal production in Şırnak was examined in terms of their education levels, it is understood that they were not graduated from University, Academy or Technical High School. In addition, when asked if they know a foreign language, it has emerged that none of the firm owner knows a foreign language. According to this situation, to increase the quality of the companies operating in Şırnak and to reduce production cost and to get to intensive production; firstly, the well trained staff in the field of minig should be employed, Research and Development R & D investments should be done and the national and international marketing opportunities should be increased. In order to achieve this, the owners of the firms of Commerce and Industry Chamber of Şırnak should organize cost free trainings to his members about finance, marketing, total quality management seminars and on foreign language english, Arabic and so on , in order to integrate with the world economy. As a result, a number of results have emerged. The solution suggestions obtained in the light of concrete datas attained from the evaluation of the results will help removing the deep-seated problems.
A General Outlook on the Socio-Economic Conditions of the Owners of the Companies Operatıng in the Trade Branch of Coal Mining in Şırnak City – 2010